Current-Voltage characteristics of polymethylthiophene/TiO2 nanocomposite cells - Trung, Vu Quoc; Tinh, Thai Doan; Dieu, Tran Vinh; Pfleger, Jiri (Vietnam Journal of Chemistry, 2014)
Titanium oxide nanoparticles (TiO2) were combined with polymethylthiophene (PMT), giving nanocomposites in core-shell structure via chemical polymerization. In this work, the current - voltage characteristics of sandwich cells composed from such nanocomposite have been studied. For these investigations films of nanocomposites were prepared by electrophoretic deposition (EPD).